AnAlysis of the quAsi-rents gener Atedin the mobile telephony mArket - Nova Arévalo, Néstor A; Pinzón Rueda, Wilson A; Meza Álvarez, Joaquín (Ingeniería Solidaria, 2012)
The regulatory model of the mobile telecommunications market works in some countries in the Americas and Europe and is justified by a global regulatory entity; it has the effect of increasing the rates of mobile post-paid phone plans. The author does a statistical analysis of the regulatory effect on the economicbehavior of the mobile phone post-paid plans market in some regions of the world in order to identify the quasi-rents received by service operators based on their hold in the market. This paper was conducted in the year 2011 as part of the development of a Masters thesis in Industrial Engineering attached to the Universidad Distrital Francisco José de Caldas.
Keywords: quasi-rents; coercitive intervention; economic regulation; mobile phones